2018
DOI: 10.1098/rstb.2017.0328
|View full text |Cite
|
Sign up to set email alerts
|

The same but different: cell intercalation as a driver of tissue deformation and fluidity

Abstract: The ability of cells to exchange neighbours, termed intercalation, is a key feature of epithelial tissues. Intercalation is predominantly associated with tissue deformations that drive morphogenesis. More recently, however, intercalation that is not associated with large-scale tissue deformations has been described both during animal development and in mature epithelial tissues. This latter form of intercalation appears to contribute to an emerging phenomenon that we refer to as tissue fluidity—the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Recent work has suggested that tissues can undergo “solid-to-liquid” transitions, allowing cell rearrangements and thus driving morphogenetic events such as Drosophila germband elongation (e.g., Tetley and Mao, 2018; Yan and Bi, 2019). This event involves modulation of both cytoskeletal contractility and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that tissues can undergo “solid-to-liquid” transitions, allowing cell rearrangements and thus driving morphogenetic events such as Drosophila germband elongation (e.g., Tetley and Mao, 2018; Yan and Bi, 2019). This event involves modulation of both cytoskeletal contractility and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Such intercalation events could be triggered by local tension in the epithelium as described in other systems (e.g. Aigouy et al, 2010) and could thereby serve to maintain tissue fluidity and reduce anisotropy in tissue tension (Tetley and Mao, 2018; Tetley et al, 2019). A recent preprint examines this process in further detail (Jain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As segments annelids can form from single-cell-wide precursors [9], daughter cells emerge during elongation process of the ring ( Figure S1e-g). The rosette pattern being treat as an inter phase of the elongation process [41]. The boundary cells constraint the cell ow within each ring which may explain the rosette pattern formed near the boundary of the ring.…”
Section: (B) Topological Structure Proprieties and Developmentmentioning
confidence: 99%